Follower Position Does Not Affect Waggle Dance Information Transfer - Parry M. Kietzman; P. Kirk Visscher (Psyche: A Journal of Entomology)
It is known that the honey bee waggle dance communicates the distance and direction of some item of interest, most commonly a food source, to nestmates. Previous work suggests that, in order to successfully acquire the information contained in a dance, other honey bees must follow the dancer from behind. We revisit this topic using updated methodology, including a greater distance from the hive to the feeder, which produced longer, more easily-read dances. Our results are not congruent with those of earlier work, and we did not conclude that honey bees must follow a dancer from behind in order to obtain the dance information. Rather, it is more likely that a follower can successfully acquire a dance’s information regardless of where she may be located about a dancer.